Simple Design and Build Automatic Transfer Switch Generator Set On Airport Power Station With Failurea Indicator Protection - Catra Indra Cahyadi; Yanti Daryanti; Ahmad Bahrawi (Universitas Bengkulu, 2021)
Electricity needs at airports are in dire need of backup and additional supplies apart from the main PLN source, such as generator sets. It is necessary to design a simple Automatic Transfer Switch that is connected to the main source operating failure indicator to a backup energy source. Research developed in order to provide benefits to airport operational management companies so that they are safe against energy needs in the event of an energy disturbance. Panel ATS is an abbreviation of the word Automatic Transfer switch, this tool serves to move the connection between one voltage source and another electrical voltage source automatically. The research was conducted by making ATS design. To ensure the design is appropriate and functioning properly, the panel tool is tested to function properly and can operate as desired. In carrying out the test, there are 3 ways, namely manual system testing on generator sets, manual system testing on modules and automatic systems. measurement data is carried out at the time of testing automatically as well as seeing the function of each component running well. The results of the design that have been made can be used as a backup energy source if the main energy source is disturbed or trouble shooting or in an emergency, even if the energy source can function when the airport is operating and does not interfere with airport operations. manual testing and automatic interchange switch can switch power sources to load with an average time of 4.09 seconds.